The surgical management of metastatic pancreatic acinar cell carcinoma and associated pancreatic panniculitis—A case report and literature review. (2020) - Clarke, Edward M.; Stevens, Sean G.; Bennett, Tim; Crowley, Peter; Starkey, Graham
Highlights: Pancreatic acinar cell carcinoma (ACC) may present with pancreatic panniculitis. Complete surgical resection of ACC can successfully treat pancreatic panniculitis. Aggressive surgery for ACC can lead to prolonged disease-free survival. Abstract: Introduction: Pancreatic panniculitis is a rare manifestation of benign and malignant pancreatic disease. The presentation of pancreatic panniculitis is non-specific and thus diagnosis is often delayed. When associated with malignancy, pancreatic panniculitis confers a poor prognosis. This case demonstrates the successful surgical management of this paraneoplastic phenomenon following resection of the underlying pancreatic acinar cell carcinoma and associated liver metastasis. Presentation of case: A 71-year-old female with debilitating subcutaneous lower limb lesions had a delayed diagnosis of pancreatic panniculitis. A formal diagnosis of pancreatic acinar cell carcinoma with liver metastasis was established and the disease was determined to be resectable. Pre-operatively, serum lipase measured 10, 825 U/L. The patient proceeded to an open left hemihepatectomy and radical distal pancreatectomy with complete resection of malignant disease. Six days post-operatively the serum lipase levels normalised, and the panniculitis began to settle. The patient proceeded to adjuvant FOLFORINOX chemotherapy. Twenty months post-surgery, the patient remains disease-free and without any evidence of panniculitis. Discussion: Due to the rarity of pancreatic acinar cell carcinoma, guidelines based on prospective data do not exist. Most management is based on retrospective analyses. A survival benefit may be achieved with more aggressive surgical management compared to other pancreatic cancer types. Pancreatic acinar cell carcinoma may show a slower rate of disease progression, an increased likelihood of resectability of disease at presentation and is more likely to undergo potentially curative resection. Conclusion: Aggressive surgical management of resectable metastatic pancreatic acinar cell carcinoma can treat pancreatic panniculitis and provide sustained disease-free survival from pancreatic cancer.